Interference effects on the wind load evaluation of a high building group by wind tunnel tests - Wittwer, Adrián Roberto (2015)
Fil: Wittwer, Adrián Roberto. Universidad Nacional del Nordeste. Facultad de Ingeniería. Laboratorio de Aerodinámica; Argentina.